PEMBERDAYAAN MASYARAKAT MELALUI INOVASI BATIK DAN PRODUK MAKANAN MANGROVE DI DESA TANJUNG REJO KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Muhammad Yasir,; Fitria Wardani,; Apliniari Yuniar,; Ardhansyah Putra Hrp, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Mangroves are typical plants found in coastal areas. Mangrove batik motifs as coastal plants have not been exposed optimally. Meanwhile, the coastal environment with its flora and fauna has tremendous potential as a batik motif. Aside from being a motif, mangrove plants can also be used as natural batik dyes and mangroves can be processed into food and beverage ingredients which are currently becoming a trend in the community. The use of mangroves as natural dyes, in addition to providing natural colors and beautiful motifs, can also reduce environmental pollution. The method of implementing the activities is group-based, comprehensive assistance is provided in all aspects, starting from providing facilities and infrastructure, as well as improving various HR skills through training. To increase the selling value of the mangrove crafts produced, foster partners were given training to diversify batik products in the form of brooches, wallets, bags and exhibitions of food and drink made from mangroves. The results of this service activity can provide more varied motifs and patterns of mangrove batik. Besides that, it resulted in the diversification of mangrove batik products into brooches, wallets and bags which have a higher selling value than just sheets of cloth. The fostered partners participated in the exhibition to further introduce the results of mangrove batik to the community and related agencies.